RESIDUAL EFFECT OF TILLAGE THE SOIL AND DISPLACEMENT SPEED IN THE SEEDER OPERATION OF THE Crotalaria juncea - CORTEZ, Jorge Wilson; Angeli FURLANI, Carlos Eduardo; SILVA, Rouverson Pereira da; Checchio GROTTA, Danilo César (Scientia Agraria, 2008)
The sowing operation is very important for the establishment of cultures, being her responsible for great costs. The objective of the present work was to evaluate the performance of an agricultural tractor in the operation of Crotalaria juncea sowing in soil under two tillages (conventional and no-tillage) and three marches imposed to the tractor that provided theoretical forward speeds of 4, 5 and 7 km h-1. The experiment was driven in experimental field of UNESP of Jaboticabal, SP, Brazil, driven by the technical team of the Laboratório de Máquinas e Mecanização Agrícola (LAMMA) in design completely with factorial array 2 x 3 with four repetitions. They were measured: drawbar force, drawbar power in the bar, field capacity, energy consumption, fuel consumption and travel reduction. The results indicated that there is no difference for the systems tillage as for the parameters of acting of the tractor. When the choice of the march, the largest increase the power, the field capacity and the fuel consumption (L h-1) and reduce the time of work for hectare, of the field consumption and specific consumption.